Effects of Teleassistance on the Quality of Life of People With Rare Neuromuscular Diseases According to Their Degree of Disability - Martínez, Oscar; Amayra, Imanol; López-Paz, Juan Francisco; Lázaro, Esther; Caballero, Patricia; García, Irune; Rodríguez, Alicia Aurora; García, Maitane; Luna, Paula María; Pérez-Núñez, Paula; Barrera, Jaume; Passi, Nicole; et al. (Frontiers in Psychology, 2021)
Rare neuromuscular diseases are a group of pathologies characterized by a progressive loss of muscular strength, atrophy, fatigue, and other muscle-related symptoms, which affect quality of life levels. The low prevalence, high geographical dispersion and disability of these individuals involve difficulties in accessing health and social care services. Teleassistance is presented as a useful tool to perform psychosocial interventions in these situations. The main aim of this research is to assess the effects of a teleassistance psychosocial program on the quality of life levels of people with rare neuromuscular diseases who have different levels of disability. A sample of 73 participants was divided into an experimental group (n = 40), which participated in the intervention, and a control group (n = 33). Quality of life was evaluated through the SIP and the SF-36, and disability through the WHO-DAS II. The participants with a moderate to severe level of disability were those who most benefited from the intervention. The results also revealed that the psychosocial teleassistance program was suitable to improve physical and psychosocial aspects of people suffering from a rare neuromuscular disease with a moderate level of disability, but just psychosocial aspects in those with a severe level of disability.